Efficacy and Safety of Dapagliflozin Monotherapy in Patients with Insulin Resistance Syndrome and Relative Insulin Deficiency: Dapagliflozin in Insulin Resistance - Hamza, Amir; Bari, Abdul; Azam, Muhammad; Wahid, Abdul; Bakhsh, Allah; Asma, Bibi (Pakistan Journal of Health Sciences, 2025)
Type 2 diabetes mellitus had different subtypes. Some patients had insulin resistance syndrome, while others had relative insulin deficiency. Dapagliflozin helped in both subtypes. It reduced blood sugar, weight, and improved heart health. It works with independent of insulin. Objective: To evaluate efficacy and safety of dapagliflozin monotherapy in patients with insulin resistance syndrome and relative insulin deficiency. Methods: This Prospective Quasi-Experimental Study Design was conducted at Bolan Medical College and Jhalawan Medical College Hospital between January 2024 and December 2024. A total of 180 T2DM patients (aged 30-70 years) received 10mg dapagliflozin monotherapy. Age, HbA1c, weight, glucose, and blood pressure were recorded at baseline and after three months. Patients were classified patho-physiologically as insulin resistance syndrome and relative insulin deficiency. Results: The most common age group was 41–50 years (65, 36.1%). The mean age was 54.3 ± 2 years. Males were 100 (55.6%) and females were 80 (44.4%). At baseline, HbA1c was 7.8 ± 0.5% and 8.3 ± 0.4%, glucose 158 ± 15.2 and 162 ± 14.5. At the 3-month follow-up, both groups showed reductions in HbA1c (−1.2 ± 0.4% in IRS vs. −1.0 ± 0.3% in RID), fasting plasma glucose (−22 ± 5.1 mg/dL vs. −18 ± 4.8 mg/dL), and body weight (−3.5 ± 1.0 kg vs. −2.2 ± 0.8 kg). Conclusion: Dapagliflozin improves glycemic control and weight control by reducing sugar in the urine in both insulin resistance syndrome and renal insufficiency disease patients.